EPIDEMIOLOGICAL CHARACTERISTICS OF THYROID CANCER IN THE DEVELOPED INDUSTRIAL REGION - R. M. Idiatullin; S. N. Styazhkina (Сибирский онкологический журнал, 2020)
The purpose of the study was to assess thyroid cancer epidemiology in the Udmurt Republic during 2008–18 and to estimate thyroid cancer raetes until 2023.Material and Methods. The incidence of thyroid cancer in the Udmurt Republic was studied over a 10-year period (2008–18) according to state statistical accounting and reporting documentation.Results. The age-standardized incidence rate of thyroid cancer in the Udmurt Republic for both sexes increased from 2.57 ± 0.36 per 100,000 population in 2008 to 6.60 ± 0.61 per 100,000 population in 2018, with an average annual percentage change of 9.9 %. The mortality rate from thyroid cancer decreased from 0.39 ± 0.12 per 100,000 population in 2008 to 0.36 ± 0.14 per 100,000 population in 2018.The incidence of thyroid cancer in the Udmurt Republic in 2023 was estimated to be 10.24 per 100,000 population.Conclusion. In the Udmurt Republic, the increase in the incidence of thyroid cancer is significantly higher than in the Volga Federal District and Russia. The obtained estimates of thyroid cancer incidence until 2023 can be used in developing programs for early detection and prevention of this disease.